Rhetorical Features of National Newspaper Headlines - Daphnee Joy Carpio; Jalleah Marie Besa; Rochelle Consejo; Karen Jean Sesbreno; Ruel Bonganciso (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2024)
Headlines wield immense influence in newspapers, being the primary conveyors of key messages while concurrently piquing reader interest and visually conveying innovative concepts. Therefore, our study analyzes the stylistic intricacies within National Newspaper Headlines, with specific emphasis on Rhetorical Features. To realize this objective, we adopted a Stylistic Analysis research framework, employing a lottery method and an observational checklist as our data collection tools. Employing a simple random sampling method, we carefully selected headlines from diverse national media company websites. To ensure validity, we determined the necessary sample size using the reliable Slovin formula. Upon analysis of our gathered data, a distinct pattern emerged. The use of metonymy emerged as the predominant stylistic element within national newspaper headlines. Remarkably, journalists from these media entities used this feature to deliver clarity and enhance overall readability, effectively underscoring its role in facilitating communication. In conclusion, our study delves into the detailed patterns of style found in national newspaper headlines. Our research highlights how journalists skillfully use these style elements not only to share information but also to grab readers’ attention and affect how people interpret news headlines.